HUBUNGAN PENDIDIKAN IBU DAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING DI DESA TB WILAYAH KERJA PUSKESMAS CIBADAK TAHUN 2019 - Rita Ariesta; Neneng Rahmawati (Akademi Kebidanan La Tansa Mashiro, 2020)
According to data obtained from the Lebak District Health Office in 2018, the highest stunting incidence occurred in Mount Kencana at 492, the second highest incidence occurred in Pamandegan sub-district at 156 and the third highest stunting incidence occurred in Cipanas at 132 based on these data with the location The area that is the easiest to reach is TB Village and the researchers conducted research in the work area of the Cibadak Health Center. The purpose of this study was to find out whether there was 2019. The study used a 1:1 case control analytic design with the relationship between maternal education and exclusive breastfeeding with the incidence of stunting in children aged 6-12 years